Angiomyolipoma of the broad ligament - Satya Dutta; Evarisalin Marbaniang; Biswajit Dey; Bifica Sofia Lyngdoh; Vandana Raphael (University of São Paulo, 2021)
Angiomyolipoma is a benign mesenchymal neoplasm of the renal parenchyma, accounting for 1% of all renal parenchymal tumors. However, this entity may rarely occur in extrarenal sites. Extrarenal angiomyolipoma has been documented in various sites of the body, but angiomyolipoma of the broad ligament was reported in only two cases. We report the reputed third case of angiomyolipoma of the broad ligament in a 33-year-old female, who presented clinically with abdominal distension. With a working diagnosis of low-grade neoplasm, an en-bloc excision of the left broad ligament mass was performed. Based on histopathology and immunohistochemistry, a diagnosis of the classical variant of angiomyolipoma of the left broad ligament was made. The post-operative period was uneventful with no recurrence after 6 months of follow-up